Phalangeal fracture in a 60-year-old man after a low-voltages electric shock - Yi Zhang; Jiaquan Yang; Kunqiang Chen; Song Zhou; Liangliang Zhou; Shiguo Gong; Ronghui Xie; Zhigang Zhou (Medicine, 2026)
Rationale: Fractures caused by low-voltage electric shocks are extremely rare, especially those involving the distal appendicular skeleton. Most reported cases involve the proximal skeleton, such as the shoulder or vertebrae, and phalangeal fractures following low-voltage shocks without direct mechanical trauma have not been reported previously. Patient concerns: A 60-year-old man presented with persistent pain, swelling, limited thumb motion, and a non-healing ulcer after sustaining a 220V household electric shock to his left thumb. The patient reported falling onto his buttocks immediately after the shock but did not sustain any direct trauma to the injured thumb. Diagnoses: Initial physical examination revealed pain and restricted thumb mobility, accompanied by an electric burn. Twenty-five days later, an X-ray demonstrated a comminuted fracture of the left thumb phalanx with associated soft tissue injury. Interventions: The patient underwent stepwise surgical management, including debridement of necrotic tissue, bone cement filling, and subsequent interphalangeal joint fusion with Kirschner wire fixation. Perioperative antibiotics were administered according to microbial culture results. Outcomes: The wound healed well after staged surgeries. Radiographs at one month showed callus formation, and at 6 months follow-up, the patient regained pain-free thumb function adequate for daily activities with stable bone healing. Lessons: Although extremely rare, this case suggests that low-voltage electric shocks may occasionally cause fractures in the absence of direct trauma through tetanic muscle contraction. Clinicians should maintain a high index of suspicion for occult fractures in patients with localized finger pain after electric injuries and perform radiographic evaluation promptly to avoid missed diagnoses.